Clinical characterisation of Becker muscular dystrophy patients predicts favourable outcome in exon-skipping therapy. Issue 1 (10th May 2013) - van den Bergen, J C; Schade van Westrum, S M; Dekker, L; van der Kooi, A J; de Visser, M; Wokke, B H A; Straathof, C S; Hulsker, M A; Aartsma-Rus, A; Verschuuren, J J; Ginjaar, H B
Abstract : Objective: Duchenne and Becker muscular dystrophy (DMD/BMD) are both caused by mutations in the DMD gene. Out-of-frame mutations in DMD lead to absence of the dystrophin protein, while in-frame BMD mutations cause production of internally deleted dystrophin. Clinically, patients with DMD loose ambulance around the age of 12, need ventilatory support at their late teens and die in their third or fourth decade due to pulmonary or cardiac failure. BMD has a more variable disease course. The disease course of patients with BMD with specific mutations could be very informative to predict the outcome of the exon-skipping therapy, aiming to restore the reading-frame in patients with DMD. Methods: Patients with BMD with a mutation equalling a DMD mutation after successful exon skipping were selected from the Dutch Dystrophinopathy Database. Information about disease course was gathered through a standardised questionnaire. Cardiac data were collected from medical correspondence and a previous study on cardiac function in BMD. Results: Forty-eight patients were included, representing 11 different mutations. Median age of patients was 43 years (range 6–67). Nine patients were wheelchair users (26–56 years). Dilated cardiomyopathy was present in 7/36 patients. Only one patient used ventilatory support. Three patients had died at the age of 45, 50 and 76 years, respectively. Conclusions: This study provides mutation specific data on the course of disease in patients with BMD. It shows that the disease course of patients with BMD, with a mutation equalling a 'skipped' DMD mutation is relatively mild. This finding strongly supports the potential benefit of exon skipping in patients with DMD.